2020
DOI: 10.1038/s41598-020-67345-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic phospholipase A2-α participates in lipid body formation and PGE2 release in human neutrophils stimulated with an l-amino acid oxidase from Calloselasma rhodostoma venom

Abstract: Cr-LAAO, an l-amino acid oxidase isolated from Calloselasma rhodosthoma snake venom, has been demonstrated as a potent stimulus for neutrophil activation and inflammatory mediator production. However, the mechanisms involved in Cr-LAAO induced neutrophil activation has not been well characterized. Here we investigated the mechanisms involved in Cr-LAAO-induced lipid body (also known as lipid droplet) biogenesis and eicosanoid formation in human neutrophils. Using microarray analysis, we show for the first time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…Many lipid metabolism-related genes were in cluster 2 in both inoculum cohorts. This includes: PLA2G4A, which encodes a phospholipase involved in membrane lipid remodeling and biosynthesis of lipid mediators of the inflammatory response [ 34 , 35 ]; GPR84 , which serves as a receptor for free fatty acid [ 36 ]; CD5L , which encodes a regulator of lipid synthesis that in turn regulates inflammatory response mechanisms and T cell activities [ 37 ]; and ALOX15 , which encodes a lipoxygenase that catalyzes the deoxygenation of polyunsaturated fatty acids and has known roles in red cell maturation and the inflammatory immune response [ 38 ]. Several lipid metabolism-related genes that were in cluster 2 in the low inoculum cohort were in cluster 3 in the high, indicating that they continued to increase expression levels throughout infection and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Many lipid metabolism-related genes were in cluster 2 in both inoculum cohorts. This includes: PLA2G4A, which encodes a phospholipase involved in membrane lipid remodeling and biosynthesis of lipid mediators of the inflammatory response [ 34 , 35 ]; GPR84 , which serves as a receptor for free fatty acid [ 36 ]; CD5L , which encodes a regulator of lipid synthesis that in turn regulates inflammatory response mechanisms and T cell activities [ 37 ]; and ALOX15 , which encodes a lipoxygenase that catalyzes the deoxygenation of polyunsaturated fatty acids and has known roles in red cell maturation and the inflammatory immune response [ 38 ]. Several lipid metabolism-related genes that were in cluster 2 in the low inoculum cohort were in cluster 3 in the high, indicating that they continued to increase expression levels throughout infection and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological action of PLA2 and other venom toxins also involve the enzymatic mobilization of cPLA2 and increased expression of COX-2. Additionally, more recent data show that the action of COX-2 seems to be crucial for the edema course [20,[32][33][34][35][36]. Other studies [34] suggest that GA may also potentially inhibit the COX-2 activity and increase AA levels.…”
Section: Institutional Review Board Statementmentioning
confidence: 97%
“…Additionally, more recent data show that the action of COX-2 seems to be crucial for the edema course [20,[32][33][34][35][36]. Other studies [34] suggest that GA may also potentially inhibit the COX-2 activity and increase AA levels. This fact may be an important factor for increased oxidative stress, raising the H2O2 and ROS, which can lead to AA peroxidation, membrane destruction, and increased edema, for example [20,21,36].…”
Section: Institutional Review Board Statementmentioning
confidence: 97%
“…During the activation of neutrophils induced by Cr-LAAO, the microarray data also demonstrated that the expression of lipid-related genes was upregulated not only due to signal transduction and metabolism genes, such as DGAT1, DGAT2, cPLA2-α, and COX-1. COX-2 and prostaglandin E synthase, as well as others, also include genes related to lipid droplet formation, including PLIN2, PLIN3, DGAT1, and DGAT2 ( Paloschi et al, 2020 ). Perilipin 3 (PLIN3) plays a vital role in the formation of LDs in neutrophils and in the release of PGE2 because when PLIN3 is downregulated by siRNA treatment, LDs in HL-60-derived neutrophils disappear, the secretion of PGE2 levels decreases by 65%, and the enzymes involved in the synthesis of PGE2 are also inhibited ( Nose et al, 2013 ).…”
Section: Lipid Droplets and Immune Cellsmentioning
confidence: 99%